Government Interventions in the Domestic Shipping Industry: A Discussion on Market Competition and Maritime Safety - Kris A. Francisco (Philippine Institute for Development Studies (PIDS), 2023)
The domestic shipping industry has a crucial role in the Philippine economy as it serves as the backbone supporting domestic trade and provides an affordable means of interisland transfer. However, the industry is riddled with inefficiencies with interrelated consequences such as high cost of shipping, low quality of services and high frequency of maritime accidents. Throughout the years, the government implemented policy reforms to improve the performance of the industry, by issuing guidelines and regulations targeted to induce market competition, encourage investments and enhance maritime safety. In this study, we discussed the evolution of policies and examined some market indications of progress vis-à-vis the areas of reform. Overall, we found some positive developments with regard to market competition, lauding the government's efforts to deregulate the industry. We also observed some indications of increased investments in domestic vessels; although comparative data reveals that the country's shipping vessels remain older and smaller, on average, than in other Asian countries. This signifies the need for more intensive strategies to induce modernization of the country's fleet. In terms of maritime safety, significant difference in maritime safety indicators is yet to be observed, despite government efforts to curtail the frequency maritime accidents.
Keywords: 330; domestic shipping; competition; deregulation; maritime safety